The Wise Book of Astronomy and Philosophy in London, Wellcome Library, MS 411 (ff. 32r-37v). - Esteban-Segura, María Laura (Masaryk University, 2019)
London, Wellcome Library, MS 411 is a one-volume codex from the late fifteenth century which holds a collection of short treatises and tracts in English and Latin on different topics including prognostications, nativities, bloodletting, medical astrology, among others. In this article, the anonymous Wise Book of Astronomy and Philosophy, written in English and held in folios 32r to 37v, is taken into consideration. The objective is threefold: (i) to examine the contents, transmission and sources of the text, (ii) to describe it from a physical standpoint, and (iii) to analyse the text’s main dialectal features in order to establish a likely place of composition. Investigation on these aspects can throw some light on the function and transmission of the text, and may also prove significant for a better understanding of it.
Keywords: Literatura inglesa - S.XII-XV - Historia y crítica; MS Wellcome 411; Middle English; Astronomy; Astrology; Philosophy; Mediaeval medicine